Capture of endothelial cells under flow using immobilized vascular endothelial growth factor. (May 2015) - Smith, Randall J.; Koobatian, Maxwell T.; Shahini, Aref; Swartz, Daniel D.; Andreadis, Stelios T.
Abstract: We demonstrate the ability of immobilized vascular endothelial growth factor (VEGF) to capture endothelial cells (EC) with high specificity under fluid flow. To this end, we engineered a surface consisting of heparin bound to poly-l -lysine to permit immobilization of VEGF through the C-terminal heparin-binding domain. The immobilized growth factor retained its biological activity as shown by proliferation of EC and prolonged activation of KDR signaling. Using a microfluidic device we assessed the ability to capture EC under a range of shear stresses from low (0.5 dyne/cm 2 ) to physiological (15 dyne/cm 2 ). Capture was significant for all shear stresses tested. Immobilized VEGF was highly selective for EC as evidenced by significant capture of human umbilical vein and ovine pulmonary artery EC but no capture of human dermal fibroblasts, human hair follicle derived mesenchymal stem cells, or mouse fibroblasts. Further, VEGF could capture EC from mixtures with non-EC under low and high shear conditions as well as from complex fluids like whole human blood under high shear. Our findings may have far reaching implications, as they suggest that VEGF could be used to promote endothelialization of vascular grafts or neovascularization of implanted tissues by rare but continuously circulating EC.